Global Development Finance 2003 Vol 1 (Analysis and Statistical Appendix) : Striving for Stability in Development Finance - World Bank (Global Development Finance, 2003)
Since the late 1990s, an essential shift has taken place in the pattern of private sector financial flows to developing countries. Debt flows have fallen sharply, while equity flows--primarily in the form of foreign direct investment--have remained comparatively robust. The shift from debt to equity ought to diminish the volatility of developing countries' external finance and improve their access to technology, markets, and management expertise. However, much more needs to be done to put development finance on a stable basis. Global Development Finance 2003 is unique in its depth of coverage of the issues related to international development finance. By putting all development-related flows in a consistent framework, the publication will allow government officials, economists, investors, financial consultants, academics, bankers, and the entire development community to better understand, manage, and promote the key challenges of financing development. Global Development Finance 2003, I: Analysis and Statistical Appendix is the World Bank's annual review of recent trends in and prospects for financial flows to developing countries. It also contains the World Bank's projections of the global outlook in view of the current global geopolitical uncertainties